Nearest-integer response from normally-distributed opinion model for likert scale. - Pornel, Jonny B. (Philippine Statistician, 2011)
This paper proposes that respondents' opinions on Likert Scale items are normally distributed around their latent ability although their observable responses will be integers in the scale nearest to those opinions. We tested the appropriateness of the model on actual data gathered by a Likert scale developed to measure attitude of teachers towards research undertaking. The soundness of common research practice of using mean and standard deviation to estimate the respondents' latent ability was tested. The results show that the NIRNDO model could be used appropriately to model responses on Likert scale. Also, the results show that using the mean response to a Likert scale, the resulting 95% confidence interval (mean + 1.96 SEM) would be effective at least 90% of the time. This effectiveness is guaranteed for latent ability in the optimum range [u + 0.8, v - 0.8] where u and v are the lowest and highest points in the scale, respectively.